The Exploration of Endophytic Fungus from Leaves Rubber Plants and Their Potential Antagonism Againts Colletotrichum gloeosporioides Leaf Fall Disease - Rani Adha Nisaq; Syamsul Bahri; Yenni Marnita; Alchemi Putri Juliantika Kusdiana (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This study aims to explore endophytic fungi found on the leaves of healthy rubber plants and determine their antagonistic potential against Colletotrichum gloeosporioides leaf fall disease in vitro using Potato Dextrose Agar media with the Dual Culture method. Almost all parts of the rubber plant can be infected with a number of plant diseases, one of which attacks the leaves. Leaf fall disease can be detrimental because fallen leaves can cause plant growth to be inhibited, and sap or latex production will decrease and can even result in death of the plant. An alternative to controlling diseases that have attacked widely is to use biological control by exploration. Exploration is carried out to obtain beneficial biological control materials and is the first step in the implementation of biological control techniques. The research was conducted using a Non-Factorial Completely Randomized Design (CRD), namely by using PDA (Potato Dextrose Agar) solid media consisting of 4 replicates, as the treatment was an isolate of endophytic fungi from exploration and the isolate tested for antagonism was the Colletotrichum gloeosporioides fungus. The results of the percentage of inhibition on endophytic fungus isolates that are able to inhibit or suppress the growth of the mycelium of the C. gloeosporioides fungus with values ranging from 40% are only found in endophytic fungus isolate C (Arthobotrys Corda) in the P3 treatment with an average percentage inhibition of 40.94% which is included in the criteria for a medium percentage of inhibition.